Սոցիալական աշխատանքի հայկական դպրոցի կայացման հիմնախնդիրը - Անտոնյան Միրա (Bulletin of Yerevan University G: Economics, 2017)
This article addresses the issues of establishment of Armenia’s own school of social work based on interconnected knowledge with sociology, and practical knowledge. The article also concentrates on the need to complete the discourse about social work scientification. Theorizing practitioner’s expertise, conducting research, and activating professional association of social workers are the essential preconditions of establishing social work’s own school.